(3fGUQ (B/s - (3CfJhfj, fGJfLs; (3TGcQs ((3GdbGgQI (B:s (3ecJHI eOHhdj ,s, 1993)
(3faPJ GdWHYI GdGhdi HYO YGe hGMO ef UOhQgG dGSHGH ef HjfgG GdcJGH jJfGhd SjQI RYje YQHj JLGhR JCKQg MOhO HdGOg Hd h efWbJg Gdi GdYGde HCSQg h NWH hOg GdbQjH h GdHYjO Ydi MO ShGA hhUag GdGYOGA bHd GdGUObGA HGdhWfjI h SMQ GdTNUjI ceG Gf GdeDda CfJhfj fGJJfL ef GdTNUjGJ GdSjGSjI GdHGQRI GdJj dYHJ OhQG gGeG aj GdSjGSI GdHQjWGfjI GP cGf jTZd efUH hRjQ GdOhdI ddTDhf GdNGQLjI aj McheI EjOf h GSJbGd ef efUHg GMJLGLG Ydi GTJQGc HdGOg aj GdYOhGf GdKdGKj Ydi eUQ aj YGe (B1956 (3gPG aVdG Yf Gf eUGOQ eYdheGJg cGfJ UOGbJg GdTNUjI GdMejejI HYHO GdfGUQ h UdGJg HZjQg ef ef GdQDSGA hQLGd GdSjGSI GdYdjejf HHhGWf GdGehQ aj efWbI GdTQb GdGhSWs
Keywords: (3JhfSs; (3YHO GdfGUQs; (3GdQFjSs